Targeted metagenomic recovery of four divergent viruses reveals shared and distinctive characteristics of giant viruses of marine eukaryotes. (25th November 2019) - Needham, David M.; Poirier, Camille; Hehenberger, Elisabeth; Jiménez, Valeria; Swalwell, Jarred E.; Santoro, Alyson E.; Worden, Alexandra Z.
Abstract : Giant viruses have remarkable genomic repertoires—blurring the line with cellular life—and act as top–down controls of eukaryotic plankton. However, to date only six cultured giant virus genomes are available from the pelagic ocean. We used at-sea flow cytometry with staining and sorting designed to target wild predatory eukaryotes, followed by DNA sequencing and assembly, to recover novel giant viruses from the Pacific Ocean. We retrieved four 'PacV' partial genomes that range from 421 to 1605 Kb, with 13 contigs on average, including the largest marine viral genomic assembly reported to date. Phylogenetic analyses indicate that three of the new viruses span a clade with deep-branching members of giant Mimiviridae, incorporating the Cafeteria roenbergensis virus, the uncultivated terrestrial Faunusvirus, one PacV from a choanoflagellate and two PacV with unclear hosts. The fourth virus, oPacV-421, is phylogenetically related to viruses that infect haptophyte algae. About half the predicted proteins in each PacV have no matches in NCBI nr ( e -value < 10 −5 ), totalling 1735 previously unknown proteins; the closest affiliations of the other proteins were evenly distributed across eukaryotes, prokaryotes and viruses of eukaryotes. The PacVs encode many translational proteins and two encode eukaryotic-like proteins from the Rh family of the ammonium transporter superfamily, likely influencing the uptake of nitrogen during infection. cPacV-1605 encodes a microbial viral rhodopsin (VirR) and the biosynthesis pathway for the required chromophore, the second finding of a choanoflagellate-associated virus that encodes these genes. In co-collected metatranscriptomes, 85% of cPacV-1605 genes were expressed, with capsids, heat shock proteins and proteases among the most highly expressed. Based on orthologue presence–absence patterns across the PacVs and other eukaryotic viruses, we posit the observed viral groupings are connected to host lifestyles as heterotrophs or phototrophs. This article is part of a discussion meeting issue 'Single cell ecology'.